Agnes Monica's Speak Action in The Kick Andy Event "Young People Who Are Worldwide" - Sahat Taruli Siahaan; Rosdiana Rajagukguk (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to explain the type of speech acts of Agnes Monica in the Kick Andy show "Yang Muda Yang Mendunia". The approach used is Pragmatics (Searle, 1983) aboaut speech act theory. The method used in this research is Descriptive Qualitative. The data of this research are clauses or utterances of Agnes Monica, a young Indonesian singer who has successfully worked in the international arena. The data source in this research is a video of Agnes Monica and Kick Andy's conversation with a duration of 15:49 minutes on Youtube on Dvichsan Sinaga's account. The results of the analysis reveal that there are 2 types of speech acts contained in Agnes Monica’s utterances in the Kick Andy talk show, that is locution (with 11 speech acts) and illocution (directive, assertive, declarative) with 21 speech acts; (2) directive illocution (with 10 findings) is the dominant type of speech act in Agnes Monica’s utterances in the Kick Andy talk show “Yang Muda Yang Mendunia”.